La constitucionalización del derecho administrativo en colombia. Análisis de la incidencia de la obra del legislador en este proceso - Santaella Quintero, Héctor (Revista de Derecho, 2019)
The constitutional consecration of values, principles and fundamental rights of second and third generation has given way to a gradual but decided process of transformation of the legal system. Even though traditionally the constitutional justice assumes the main position in this process, the legislative plays also a very important role in its development. The analysis of the last reform of the colombian administrative procedure and administrative justice Act shows clearly this situation.